DESIGN AND ANALYSIS OF APPROACH TRESTLE - M, Arunrex.; A, Dineshmanickam.; D, Eraianbu.; M, Ramkumar.; S, Subathra. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The present research work examines the operational efficiency of select major ports in in india over theperiod of time 1993 to 2011 through data envelopment analysis. Hypothesis tested in this study is, size does notdetermine port efficiency. Based on the results it is found that both bigger ports i.e. Mormugao, Jawaharlal Nehruport Trust and smaller ports Ennore, Tuticorin were proved have efficient port operations all through. Through theresult of super-efficient analysis, the study found that JNPT port rated as number one super-efficiency port amongthe selected major ports in india. Trestle works creating a hierarchical categorization tree that can be used to predictmissing attribute values and cluster sets of examples into conceptually meaningful groups. New categorizationmodel is competitive with non-incremental approaches and more closely approximate human performance